2021
DOI: 10.1016/j.prrv.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Multi-system inflammatory syndrome in children & adolescents (MIS-C): A systematic review of clinical features and presentation

Abstract: Multisystem Inflammatory Syndrome in Children (MIS-C) is a new phenomenon reported worldwide with temporal association with Covid-19. The objective of this paper is to evaluate reported cases in children and adolescents. From 1726 papers, 35 documented papers related to MIS-C cases identified 783 individual cases of MIS-C between March-June 2020; with 55% being male ( n = 435) and a median age of 8.6 years (IQR, 7–10 years; range 3 months–20 years). Patients with MIS-C were noted to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

39
532
9
64

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(644 citation statements)
references
References 40 publications
39
532
9
64
Order By: Relevance
“…As mentioned previously, two systematic reviews have been recently published that include patients with MIS-C [10,12]. However, this scoping review provides additional insight into this rapidly evolving condition as it includes several studies not included in either previous review, with MIS-C data through October 5, 2020 (compared to May 31, 2020 and June 20, 2020 in previous reviews).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned previously, two systematic reviews have been recently published that include patients with MIS-C [10,12]. However, this scoping review provides additional insight into this rapidly evolving condition as it includes several studies not included in either previous review, with MIS-C data through October 5, 2020 (compared to May 31, 2020 and June 20, 2020 in previous reviews).…”
Section: Discussionmentioning
confidence: 99%
“…Data on symptomatic management of MIS-C patients is rapidly emerging. There exists at least one systematic review on MIS-C which included data through June 2020 from 35 articles relating to 783 patients [10]. Roughly half of the primary studies included in the systematic review by Radia et al are reported in further detail here, as many did not meet eligibility criteria of this present study or did not report quantitative laboratory data.…”
Section: Introductionmentioning
confidence: 99%
“…We also want to emphasize that renal involvement has been reported too rarely, even not reported in several MIS-C series [ 3 6 ]. We are not sure how reliable it would be to suggest that an extremely rarely reported entity is caused by MIS-C before all possible diagnoses have been ruled out.…”
mentioning
confidence: 99%
“…MIS-C развивается через 2-4 недели после заражения SARS-CoV-2 [15], клинические проявления характеризуется большим разнообразием [16][17][18][19][20][21][22] (табл. 2).…”
Section: клинические проявленияunclassified
“…Пандемия коронавирусной болезни 2019 (coronavirus disease -COVID- 19), этиологически связанной с вирусом SARS-CoV-2 (severe acute respiratory syndrome coronavirus-2), привлекла внимание к новым клиническим и фундаментальным проблемам иммунопатологии заболеваний человека у взрослых [1] и детей [2] в целом и иммуновоспалительных ревматических заболеваний (ИВРЗ) в частности [3]. У взрослых клинические проявления COVID-19 варьируют от бессимптомного носительства до развития острого респираторного дистресс-синдрома (ОРДС), микрососудистой коагулопатии, макротромбозов и полиорганной недостаточности, ассоциирующихся с высокой летальностью [1].…”
unclassified